(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The trend is visible in front of the eye that technology is increasing among Indonesian users. Once Indonesian users appear to be in a period of prosperity because they can obtain high-speed technological tools. However, the acceptance of this technology needs to be studied whether because of utility or productivity or consumption or for other purposes. For this reason, this study aims to seek evidence from the views and studies of experts from field experience. First, we continue to collect literature in-depth with a descriptive qualitative approach until we find valid and reliable answers. Our data analysis method followed qualitative research experts’ direction, including the review approach, coding, and concluding. The finding is that most Indonesians are proven that the acceptance of technology is still at the lifestyle or consumptive level, not yet on the principle of benefit compared to the facilities and uses provided by technological tools. Thus, these findings become meaningful input for the awareness and learning of Indonesian users